Economic valuation for rectificatory justice :|the case of the oil spill at Turkey’s Gencelli Bay - Aslan, Beste Gün. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
On August 29, 2018, an oil spill reached to the shores of Gencelli Bay, in Foça district, İzmir—a small scenic town which is home to environmentally protected areas with high ecosystem value and where people’s livelihood depends mainly on tourism and fishery. The source of the spill was detected to be a ship en route to the ship-breaking yards in Aliağa district, one of the largest and oldest heavy industrial development zones in Turkey, with various toxic industries such as smelting plants, oil refineries, and chemical facilities. The ship soon was charged with an “on paper” administrative fine and the cleaning costs, deposited directly to the state, but far from representing the real costs of the oil spill. This thesis, first, aims to investigate to what extent this administrative fine addresses the real costs and resulting socioenvironmental injustices, and satisfies the conditions for rectificatory justice, by conducting an economic valuation of the damaged ecosystem services using IPBES’s conceptual framework. The analysis is based on an extensive desktop research and several in-depth interviews and focus groups with local stakeholders. Second, it attempts to identify the value articulating or political institutional preconditions (such as trust, rule of law, free speech and so on) for such a valuation exercise to become relevant in reaching just outcomes. The results suggest that real costs exceed the administrative fine even with a conservative economic valuation. Valuation assumptions and social and political institutions are central for a monetary compensation to make sense for operationalizing rectificatory justice.
Keywords: Oil spills -- Turkey -- Foça.; Oil spills -- Environmental aspects -- Turkey -- Gencelli Bay.; Oil spills -- Economic aspects -- Turkey -- Gencelli Bay.